Further Development of an Adaptive Joining Technique Based on Friction Spinning to Produce Pre-Hole-Free Joints - Wischer, Christian; Homberg, Werner (Key Engineering Materials)
Mechanical joining processes are an essential part of modern lightweight construction. They permit materials of different types to be joined in a way that is suitable for the loads involved. These processes reach their limits, however, as soon as the boundary conditions change. In most cases, these elements are specially adapted to the joining point and cannot be used universally. Changes require cost-intensive adaptation of both the element and the process control, thus making production more complex. This results in high costs due to the increased number of auxiliary joining element variants required and reduces the economic efficiency of mechanical joining. One approach to overcoming this issue is the use of adaptive auxiliary joining elements formed by friction spinning. This article presents the current state of research on pre-hole-free joining with adaptive joining elements. The overall process chain is illustrated, explained and analyzed. Special attention is paid to demonstrating the feasibility of pre-hole-free joining with adaptive joining elements. The chosen mechanical parameters are subsequently listed. Finally, a comprehensive outlook of the future development potential is derived.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Inverse parameter identification of an anisotropic plasticity model for sheet metal - Friedlein, J.; Wituschek, S.; Lechner, M.; Mergheim, J.; Steinmann, P. (IOP Conference Series: Materials Science and Engineering)
The increasing economic and ecological demands on the mobility sector require efforts to reduce resource consumption in both the production and utilization phases. The use of lightweight construction technologies can save material and increase energy efficiency during operation. Multi-material systems consisting of different materials and geometries are used to achieve weight reduction. Since conventional joining processes reach their limits in the connection of these components, new methods and technologies are necessary in order to be able to react versatilely to varying process and disturbance variables. For fundamental investigations of new possibilities in joining technology, numerical investigations are helpful to identify process parameters. To generate valid results, robust and efficient material models are developed which are adapted to the requirements of versatile joining technologies, for instance to the high plastic strains associated with self-piercing riveting. To describe the inherent strain-induced plastic orthotropy of sheet metal an anisotropic Hill-plasticity model is formulated. Tensile tests for different sheet orientations are conducted both experimentally and numerically to adjust the anisotropic material parameters by inverse parameter identification for aluminium EN AW-6014 and steel HCT590X. Then, the layer compression test is used to validate the model and the previously identified parameters.

Energy direction in ultrasonic impregnation of continuous fiber-reinforced thermoplastics - Popp, J.; Wolf, M.; Mattner, T.; Drummer, D. (Journal of Composites Science)
As a new and innovative processing method for fabrication for fiber-reinforced thermoplastic composites (CFRTs), the feasibility of ultrasonic welding technology was proven in several studies. This method offers potential for the direct manufacturing of CFRT–metal structures via embedded pin structures. Despite the previous studies, a deeper understanding of the process of energy input and whether fibers work as energy directors and consequently can, in combination with chosen processing parameters, influence the consolidation quality of the CFRTs, is still unknown. Consequently, the aim of this work is to establish a deeper process understanding of the ultrasonic direct impregnation of fiber-reinforced thermoplastics with an emphasis on the fiber’s function as energy directors. Based on the generated insights, a better assessment of the feasibility of direct, hybrid part manufacturing is possible. The produced samples were primarily evaluated by optical and mechanical test methods. It is demonstrated that with higher welding time and amplitude, a better consolidation quality can be achieved and that independent of the process parameters chosen in this study, no significant fiber breakage occurs. This is interpreted as a sign of a gentle impregnation process. Furthermore, based on the examination of single roving and 5-layer set-ups, it is shown that the glass fibers function as energy directors and can influence the transformation of sonic energy into thermal energy. In comparison to industrially available CFRT material, the mechanical properties are weaker, but materials and processes offer potential for significant improvement. Based on these findings, proposals for a direct impregnation and joining process are made.

Data-driven analysis of cold-formed pin structure characteristics in the context of versatile joining processes - Römisch, D.; Zirngibl, C.; Schleich, B.; Wartzack, S.; Merklein, M. (IOP Conference Series: Materials Science and Engineering)
Due to increasingly strict emission targets and regulatory requirements, especially for companies in the transport industry, the demand for multi-material-systems is continuously rising in order to lower energy consumption. In this context, mechanical joining processes offer an environmentally friendly and flexible alternative to established joining methods, especially in the field of lightweight design. For example, cold-formed cylindrical pin structures show high potentials in joining multi-material-systems without auxiliary elements. The pin structures are joined either by pressing them directly into the joining partner or by caulking with a pre-punched part. However, to evaluate the strength of the joint and to ensure the joining reliability for versatile processes, such as changing joining partners or batch variations, engineering designers currently have only limited design principles available compared to thermal joining processes. Consequently, the design of an optimal pin joint requires cost- and time-intensive experimental investigations and adjustments to design or process parameters. As a solution, data-driven methods offer procedures for structuring data and identifying dependencies between varying process parameters and resulting pin structure characteristics. Motivated by this, the paper presents an approach for the data-driven analysis of cold-formed pin structures and offers a deeper understanding of how versatile processes affect the pin characteristics. Therefore, the application of an intelligent design of experiment in combination with several machine learning methods enable the setup of a best-fitting meta-model. Resulting, the determination of a mathematical model provides the opportunity to accurately estimate the pin height considering only relevant geometrical and process parameters with a prediction quality of 95 %.

Fiber Orientation Mechanism of Continuous Fiber Reinforced Thermoplastics Hybrid Parts Joined with Metallic Pins - Popp, J.; Kleffel, T.; Römisch, D.; Papke, T.; Merklein, M.; Drummer, D. (Applied Composite Materials)
Continuous Fiber Reinforced Thermoplastic (CFRT) hybrid parts offer interesting possibilities for lightweight application, which can exceed the capabilities of mono material metal or CFRT parts. In this case, the joining technology oftentimes is the limiting factor. This study investigates a joining operation with metal pin structures which are additively manufactured via powder bed fusion featuring different diameters and tip geometries, which are inserted into the locally infrared heated CFRT part. The resulting fiber rearrangement is assessed using transmitted light microscopy, confocal laser scanning microscopy as well as micro-computer-tomography. It could be shown that for all assessed pin variants a similar distinct fiber displacement can be seen and that the pin diameter has a significant effect on the resulting fiber orientation with smaller pin diameters being advantageous because of gentle fiber displacement and reduced undulation. The tip geometry has only minor effect on the fiber orientation. Especially in the X/Y plane no systematic influence of the tip geometry on the fiber displacement could be observed. Based on the gained insights a three-stage model of the fiber orientation processes is proposed.

Determination of the Interface Structural Resolution of an Industrial X-Ray Computed Tomograph Using a Spherical Specimen and a Gap Specimen Consisting of Gauge Blocks - Busch, M.; Hausotte, T. (Key Engineering Materials)
Industrial X-ray computed tomography (XCT) is a tool for non-destructive testing and a volumetric analysis method with the ability to measure dimensions and geometry inside a component without destroying it. However, XCT is a relatively young technology in the field of dimensional metrology and thus faces several challenges. The achievement of a high measurement resolution, which is re-quired to detect small geometrical features, depends on a variety of influencing factors. In this arti-cle, the interface structural resolution (ISR) as one of the key challenges will be investigated. The two-sphere standard called the hourglass standard allows the determination of the structural resolu-tion by evaluation of the surrounding area of an ideal point contact of two spheres after the CT re-construction in form of a neck-shaped transition. Close to the contact point of the two spheres two opposing surfaces exist. Their distances from each other increase as the distance from the contact point of the two spheres increase. The determination of the distances between the spheres’ surface allows a statement about the ISR. A new developed specimen or standard with a variable gap size consisting of calibrated parallel gauge blocks allows statements about the ISR, too. Because of the higher number of probing points of the gauge block standard the results of the determined ISR are more stable compared to the hourglass standard. This paper compares the results of the computed tomography measurements for the designed interface structural resolution standard with those of the hourglass standard.

Clinching in In-situ CT – Experimental Study on Suitable Tool Materials - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (ESAFORM 2021)
In lightweight design, clinching is a cost-efficient solution as the joint is created through localized cold-forming of the joining parts. A clinch point’s quality is usually assessed using ex-situ destructive testing methods. These, however, are unable to detect phenomena immediately during the joining process. For instance, elastic deformations reverse and cracks close after unloading. In-situ methods such as the force-displacement evaluation are used to control a clinching process, though deviations in the clinch point geometry cannot be derived with this method. To overcome these limitations, the clinching process can be investigated using in-situ computed tomography (in-situ CT). However, a clinching tool made of steel would cause strong artefacts and a high attenuation in the CT measurement, reducing the significance of this method. Additionally, when joining parts of the same material, the sheet-sheet interface is hardly detectable. This work aims at identifying, firstly, tool materials that allow artefact-reduced CT measurements during clinching, and, secondly, radiopaque materials that can be applied between the joining parts to enhance the detectability of the sheet-sheet interface. Therefore, both CT-suitable tool materials and radiopaque materials are selected and experimentally investigated. In the clinching process, two aluminium sheets with radiopaque material in between are clinched in a single-step (rotationally symmetric joint without cut section). It is shown that e.g. silicon nitride is suited as tool material and a tin layer is suitable to enhance the detectability of the sheet-sheet interface.

In Situ Computed Tomography—Analysis of a Single-Lap Shear Test with Clinch Points - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (Materials)
As lightweight design gains more and more attention, time and cost-efficient joining methods such as clinching are becoming more popular. A clinch point’s quality is usually determined by ex situ destructive analyses such as microsectioning. However, these methods do not yield the detection of phenomena occurring during loading such as elastic deformations and cracks that close after unloading. Alternatively, in situ computed tomography (in situ CT) can be used to investigate the loading process of clinch points. In this paper, a method for in situ CT analysis of a single-lap shear test with clinched metal sheets is presented at the example of a clinched joint with two 2 mm thick aluminum sheets. Furthermore, the potential of this method to validate numerical simulations is shown. Since the sheets’ surfaces are locally in contact with each other, the interface between both aluminum sheets and therefore the exact contour of the joining partners is difficult to identify in CT analyses. To compensate for this, the application of copper varnish between the sheets is investigated. The best in situ CT results are achieved with both sheets treated. It showed that with this treatment, in situ CT is suitable to properly observe the three-dimensional deformation behavior and to identify the failure modes.

Friction Characterisation for a Tumbling Self-Piercing Riveting Process - Wituschek, S.; Lechner, M. (Key Engineering Materials)
Due to increasing demands regarding ecological and economic specifications in vehicle design, the effort required for production is continuously increasing. One trend is the increased use of multi-material systems, which are characterised by the use of different materials such as high-strength steels or aluminium alloys. In addition to the varying mechanical properties of the components, an increased number of variants accompanied by different geometries is leading to increasing challenges on body construction. For the assembly and connection of the individual components, conventional joining methods reach their limitations. Therefore, new joining methods are necessary, which feature properties of versatility and can adapt to process and disturbance variables. One way of achieving tailored joints is to use a tumbling self-piercing riveting process. For the design of the process route, numerical investigations are necessary for which a characterisation of the friction properties is necessary. This paper therefore investigates the contact and friction conditions that occur in a tumbling self-piercing riveting process. The individual contacts between the process components are identified and based on this, suitable processes for the characterisation of the friction factors - and coefficients are selected and performed.

Joining with Friction Spun Joint Connectors – Manufacturing and Analysis - Wischer, Christian; Steinfelder, Christian; Homberg, Werner; Brosius, Alexander (IOP Conference Series: Materials Science and Engineering)
Nowadays, the production of modern lightweight structures, like a body in white structure requires a wide variety of mechanical joining processes. To fulfill the various demands, mechanical joining processes and joining elements (JE) are used. Very often, they are adapted to the application, which leads in turn to a numerous of different variants, high costs, and loss of the process chain versatility. To overcome this drawback, an innovative approach is the usage of individually produced and task-adapted JE, the so-called friction spun joint connectors (FSJC). These connectors can be modified in shape as well as in material properties. This flexibility offers high potential for lightweight design but also increases the necessary analytical effort regarding the forming process as well as the manufactured joint's properties. Therefore, a new analysis strategy based on the Finite-Element-Method (FEM) is proposed, which numerically determines the local load bearing capacity within a given joint in order to identify the critical regions for load transfer. The process of joining element manufacturing and the analysis strategy will be described in detail and optimization results of the joints are shown. Numerical results are discussed and possible recommendations for joint manufacturing are derived.

A contribution on versatile process chains: joining with adaptive joining elements, formed by friction spinning - Wischer, Christian; Homberg, Werner (Production Engineering)

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, B.; Köhler, D.; Vorderbrüggen, J.; Troschitz, J.; Kupfer, R.; Meschut, G.; Gude, M. (Production Engineering)

Joining of CFRT-steel hybrid parts via hole-forming and subsequent pin caulking - Römisch, D.; Popp, J.; Drummer, D.; Merklein, M. (Production Engineering)

A New Non-destructive Testing Method Applied to Clinching - Lafarge, R.; Wolf, A.; Guilleaume, C.; Brosius, A. (Minerals, Metals and Materials Series)

Experimental study on joining by forming of hct590x + z and en-aw 6014 sheets using cold extruded pin structures - Römisch, D.; Kraus, M.; Merklein, M. (Journal of Manufacturing and Materials Processing)
Due to stricter emission targets in the mobility sector and the resulting trend towards lightweight construction in order to reduce weight and consequently emissions, multi-material systems that allow a material to be placed in the right quantity and in the right place are becoming increasingly important. One major challenge that is holding back the rapid and widespread use of multi-material systems is the lack of adequate joining processes that are suitable for joining dissimilar materials. Joining processes without auxiliary elements have the advantage of a reduced assembly effort and no additional added weight. Conventional joining processes without auxiliary elements, such as welding, clinching, or the use of adhesives, reach their limits due to different mechanical properties and chemical incompatibilities. A process with potential in the field of joining dissimilar materials is joining without an auxiliary element using pin structures. However, current pin manufacturing processes are mostly time-consuming or can only be integrated barely into existing industrial manufacturing processes due to their specific properties. For this reason, the present work investigates the production of single- and multi-pin structures from high-strength dual-phase steel HCT590X + Z (DP600, t0 = 1.5 mm) by cold extrusion directly out of the sheet metal. These structures are subsequently joined with an aluminium sheet (EN AW-6014-T4, t0 = 1.5 mm) by direct pin pressing. For a quantitative evaluation of the joint quality, tensile shear tests are carried out and the influence of different pin heights, pin number, and pin arrangements, as well as different joining strategies on the joint strength is experimentally evaluated. It is proven that a single pin structure with a diameter of 1.5 mm and an average height of 1.86 mm achieves a maximum tensile shear force of 1025 N. The results reveal that the formation of a form-fit during direct pin pressing is essential for the joint strength. By increasing the number of pins, a linear increase in force could be demonstrated, which is independent of the arrangement of the pin structures.

Investigation of Different Joining by Forming Strategies when Connecting Different Metals without Auxiliary Elements - Römisch, D.; Kraus, M.; Merklein, M. (Key Engineering Materials)
Lightweight constructions become more and more important, especially in the mobility sector. In this industry, the increasingly strict regulations regarding the emissions of carbon dioxide can be achieved to a certain extent by reducing the vehicle weight. Thus, multi-material systems are used. Conventional joining techniques reach their limits when joining different materials due to different thermal expansion, unequal stiffness or chemical incompatibilities. This is why additional joining elements or adhesives are used. These must be viewed critically regarding a lightweight and resource-efficient production, since they add weight or complicate the recycling process of these components. Consequently, there is a great and growing need for new versatile joining technologies in order to overcome these challenges and to be able to react to changing process parameters and boundary conditions. Joining without an auxiliary element using pin structures formed directly from the sheet metal plane is one approach to meet these challenges. These pin structures are then joined by direct pressing into the joining partner. This is possible with a variety of material combinations, but is advantageous with regard to continuous fibre-reinforced thermoplastic composites (CFRTP), as the fibres do not have to be cut when joining CFRTP using pin structures. In this paper, the formability of pin structures made of a dual-phase steel DP600 (HCT590X + Z) is investigated. The extruded pin structures are joined by direct pin pressing with an EN AW-6014 to form tensile shear specimens. Different joining strategies are investigated to compare their influence on the joint strength. The results have shown that it is feasible to form suitable pins from a DP600 dual-phase steel to produce reliable connections with an aluminium sheet joined by direct pin pressing.

Material characterisation methods for a tumbling self-piercing riveting process - Wituschek, S.; Lechner, M. (ESAFORM 2021)
The growing demands of resource-saving processes and products are leading to increasing importance of lightweight construction for the automotive industry. One approach is multi-material design, which uses high-strength steels and aluminium alloys in the production of vehicle bodies. Therefore, reliable processes for joining components with different mechanical properties and geometries are necessary. As conventional joining processes reach their limits, new versatile processes and methods are required which can adapt to different process conditions and disturbance variables. A widely used joining process to join different materials is self-piercing riveting as a joining by forming method, however it is characterised as inflexible to changing process conditions due to a linear process kinematic and rigid dies. An approach to extend the process limits is the application of a tumbling kinematic for the punch. Thus, an adapted tumbling strategy can be used to influence the joining process and to achieve a controlled material flow in order to manufacture tailored joints. For the fundamental investigation of the process, numerical investigations are necessary. In order to achieve high model quality a precise material modelling is crucial. Therefore, a characterisation of the materials HCT590X+Z and EN AW-6014 as typical materials of multi-material mixes and the rivet material 38B2 is performed. Due to the different stress conditions during tumbling self-piercing riveting suitable characterisation methods are selected and carried out.

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, D.; Sadeghian, B.; Kupfer, R.; Troschitz, J.; Gude, M.; Brosius, A. (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.

Development of a novel adaptive joining technology employing friction-spun joint connectors (FSJC) - Wiens, E.; Wischer, C.; Homberg, W. (ESAFORM)
Joints are an essential part of modern (lightweight) structures in a broad variety of applications. The reason for this is the rapidly increasing number of different material combinations needing to be joined in application areas like the automotive industry. It is currently common to use numerous auxiliary or standardized elements instead of individually adapted joining elements. This leads to a large number of different joining elements per product and thus to high costs. An innovative approach to overcoming this issue is the design, manufacture and setting of joint-specific joining elements. A good candidate for the manufacture of adapted joining elements of this type is the so-called friction spinning process. The joining elements formed in this way can be specifically adapted to the application in question in terms of both shape and mechanical properties. The part geometry required for the properties of a given joint is formed using a universal forming tool. This makes it possible to form a wide variety of sub geometries for the auxiliary joining part as a function of the prevailing joint condition, using a single forming tool and starting from the same semi-finished bar material. By applying different process strategies for the rotational speed and feed rate during the forming operation, the same part geometry can even be given different local mechanical properties. The following contribution presents the results of ongoing research work and includes the process concept, process properties, tooling and the results of experimental investigations into the joining of two sheet metal parts with help of this new joining process.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)